Practical value of genotypic analysis for diagnosing lymphoproliferative disorders. Issue 2 (February 1987) - O'Connor, N T; Gatter, K C; Wainscoat, J S; Crick, J; Jones, D B; Delsol, G; Ralfkiaer, E; De Wolf-Peeters, C; Angus, B; Mason, D Y
Abstract : The value of DNA hybridisation (using immunoglobulin and T cell receptor gene probes) was assessed during the diagnosis of problematical lymphoid tissue biopsy specimens. In 14 of 18 specimens (78%), which contained a malignant lymphoproliferation of uncertain aetiology, this technique permitted the demonstration of a monoclonal proliferation of B cells (nine cases) or T cells (five cases). In five further lymph node biopsy specimens, in which the differential diagnosis lay between a reactive or malignant process, a clonal proliferation was shown in three cases. DNA analysis is, therefore, of practical value in resolving many of the diagnostic problems that arise in the assessment of lymphoid tissue biopsy specimens.